The Influence of Social Capital on Food Security of Farmers Household in Langlang Village Singosari District Malang Regency: Social Capital and Food Security (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2024)
Background and purposes - Food insecurity in farming households is an issue that needs attention. Farmers must have resources to support their household life, one of which is social capital. This research aims to analyze the influence of social capital and sociodemographic factors on the food security of farming households and describe the level of food security of farming households in Langlang Village, Singosari District, Malang Regency. Methodology - The research approach uses quantitative methods and ordinal regression analysis to determine the influence of social capital and sociodemographic factors on food security. Meanwhile, the Food Consumption Score (FCS) is used to determine the level of food security of farming households. The software used for data analysis is STATA 15. The analysis in this study uses significance levels of 1%, 5%, and 10%. Findings - The results show that the average food security score of farming households is 40.29, which falls within the borderline food security scale. Furthermore, sociodemographic factors that positively and significantly affect household food security include education level, farmer income, agricultural productivity, and loans/credit. In addition, social capital has a positive and significant effect on food security.